Exports and the shadow economy: Non-linear effects. Issue 7 (2nd October 2020) - Canh, Phuc Nguyen; Dinh Thanh, Su
Abstract : This study is the first attempt to investigate the non-linear impacts of export diversification and export quality on the shadow economy. Using a global sample of 116 countries over the period 2003–2014 and applying for panel econometric techniques, we find that the effects of export diversification and export quality are nonlinear on the shadow economy, respectively. The non-linear effects are also consistently found for low- and middle-income economies and high-income economies. The results are robust through different measures of shadow economy and control variables. Our findings show that this is a tipping point in the relationship of export diversification and export quality with the shadow economy. That is, when moving beyond the tipping point, both export diversification and export quality could reduce the shadow economy. This implies that trade liberalization towards export diversification and export quality is an important factor for curbing the shadow economy.